2016
DOI: 10.1016/j.amjsurg.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy hospital resource utilization in octogenarians

Abstract: Background Although pancreaticoduodenectomy (PD) is feasible in patients ≥ 80 years, little is known about the potential strain on resource utilization. Methods Outcomes and inpatient charges were compared across age cohorts (I: ≤ 70, II: 71 – 79, III: ≥ 80 years) in 99 patients who underwent PD (2005–2013) at our institution. The generalized linear modeling approach was used to estimate the impact of age. Results Perioperative complications were equivalent among cohorts. Increasing age was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…A few reports also showed that patients aged over 80 years were more likely to require some form of rehabilitation and home nursing supports following PD. 40,41 This would partly reflect the higher rate of complications noted in patients aged 80 and over. The magnitude or grading of complications and how they impacted length of stay were not well reported in the studies examined.…”
Section: Discussionmentioning
confidence: 99%
“…A few reports also showed that patients aged over 80 years were more likely to require some form of rehabilitation and home nursing supports following PD. 40,41 This would partly reflect the higher rate of complications noted in patients aged 80 and over. The magnitude or grading of complications and how they impacted length of stay were not well reported in the studies examined.…”
Section: Discussionmentioning
confidence: 99%
“…The population aged 80 or over is increasing worldwide, constituting around 1% of the overall population and is predicted to increase four‐fold by 2050 . This has imposed a new challenge for the healthcare system, given that 70% of cancer is expected to occur in the elderly . Pancreatic cancer has an incidence that increases with the age and therefore surgical options such as pancreaticoduodenectomy (PD) need to be considered more frequently in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing younger patients versus those .80 years of age, the study demonstrated that complication rate (40% vs 43%), mortality rate (4% vs 0%), and overall median survival for pancreatic cancer patients were not statistically different between the groups. 5 Langan et al 6,7 assessed 99 elderly patients from 2005 to 2013 and demonstrated that increased age was associated with increased intensive care unit stay, length of stay, and discharge to a skilled facility for rehabilitation. However, octogenarians had equivalent charges and outcome measure when compared with septuagenarians.…”
Section: Factors Associated With Postoperative Complicationsmentioning
confidence: 99%
“…6 They also suggest that it is possible to deliver quality pancreatic surgical care to an aging population without substantial increase in resource utilization. 7 Rather than chronologic age, it is more important to consider patient's performance status and comorbidities and base the decision to operate on a careful and individual risk-benefit analysis.…”
Section: Factors Associated With Postoperative Complicationsmentioning
confidence: 99%